Active matrix metalloproteinase‐8: A potential biomarker of oral systemic link. Issue 1 (19th November 2021) - Umeizudike, Kehinde; Räisänen, Ismo; Gupta, Shipra; Nwhator, Solomon; Grigoriadis, Andreas; Sakellari, Dimitra; Sorsa, Timo
Abstract: Objectives: This mini review aims to address some possible gaps in periodontal diagnosis in clinical studies particularly involving the oral‐systemic connection with a view to minimize such gaps, and thus improve patient treatment experiences and outcomes. Methods: The conventional assessment of periodontitis has traditionally been by clinical and radiographic oral parameters. We reviewed numerous studies published mainly within the past decade, to affirm the oral‐systemic link, the contribution of periodontitis to the inflammatory burden in various systemic diseases and conditions, and the potential role of active matrix metalloproteinase‐8 (aMMP‐8). Results: While it is established that periodontal pathogens in dental plaque biofilm are the primary initiating agents in periodontitis, it has become clear from the appraisal of recent studies that the host inflammation, including biomarkers such as aMMP‐8 play a major role, being the driving underlying pathological mechanism in both periodontitis and systemic diseases. Conclusions: The apparent limitations of conventional diagnostic tools have led researchers to seek alternative methods of evaluation such as the quantification of biomarkers including aMMP‐8, which can be a bridge between oral/periodontal and systemic diseases; aMMP‐8 can form a mouth‐body connection.